The spiritual enhancement programmes and activities of Sultan Haji Ahmad Shah Mosque CENTRIS in Gombak (part ii) - Fatah Yasin, Raudlotul Firdaus (Centre for Islamisation (CENTRIS), IIUM, 2024)
Under the purview of SHAS Mosque CENTRIS, SHAS Mosque was able to host a number of helpful programs and activities as of February 2022. In addition, it separated its members into three distinct services, each of which had a unique role inside the organisation. These services included the Imam and Da'wah Unit, the Management and Finance Unit, the Training and Iqra Unit, and more. The 'Ilaj and Irshad Unit, under the control of SHAS Mosque CENTRIS, was established in 2020 as a small unit to support the university's mental health task force.